Control of zootechnology leads to improved cuttlefish (Sepia officinalis, L.) reproduction performance up to pre-industrial levels - Capaz, Juan C. (2020)
Cephalopods are gaining momentum as an alternate group for aquaculture species diversification, not only because they are a good food source (highly appreciated in some worldwide markets) but they also have the potential to quickly reach a market size. However, there are some bottlenecks impeding the transition of culture technology from the laboratory to industry. One is related to control over reproduction in captivity. The objective of the present experiment was to verify the effects of tanks with different bottom areas/volumes on the reproduction performance of S. officinalis breeding stocks, when sex ratios were controlled a priori; and the food cost associated with such performance when individuals are fed a natural frozen diet. One hundred and ninety two juvenile cuttlefish were used to compare three different round-shaped tanks: one type with 3000L volume and two types with 9000L volume (with differences in bottom areas and water column). Individuals had their sex and maturity stage determined to establish a sexual ratio of 2♀:1♂ per tank and assure that cuttlefish were still immature. Biological data was collected during both growth and reproduction stages and until the death of all females in each tank. The experiment lasted nearly 300 days. Temperature differences between tank types were registered during both stages. The optimizing of rearing conditions has allowed for higher growth and a higher amount of cuttlefish available for breeding purposes. A total of 123,751 eggs (in 85 batches) was obtained during this experiment, which is a number that may meet a small scale cuttlefish commercial hatchery facility requirements. The present conditions contributed to a better and predictable reproduction performance in specific 9000L tanks, with values reaching pre-industrial numbers (≈ 24,000 eggs/tank). Moreover, both the amount of eggs per batch and the overall quality of eggs has increased. Three of these 9000L tanks have an overall consumption of ≈ 38.64 Kg tank–1, which translates in an investment in feed of ≈ 193 € tank–1, 8.40 € per cuttlefish and an overall daily tank expense of 1.76 € d–1.